2014
DOI: 10.5398/medpet.2014.37.2.129
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Rumen Fermentation of Ration Supplemented with Protected Vegetable Oils

Abstract: This experiment was designed to evaluate the effects of protected vegetable oils supplementation on in vitro fermentation characteristics, rumen microbial population, and methane production in cattle. The treatments were arranged in a complete randomized block design involving 2 factors i.e. oil type (sesame, canola, and flaxseed) and protection methods (non protected, calcium soap, and microencapsulation). Variables observed were rumen pH, N-NH 3 , total and molar proportion of VFA, dry matter and organic mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 29 publications
3
13
0
8
Order By: Relevance
“…The average variable values of rumen fermentation were in normal range which indicated that the supplementation of 5% SOCS and 10% CFF in the rations did not give significant negative effect on the digestion process in the rumen. Voigt et al (2006) reported that calcium salts of long-chain fatty acid are insoluble at ruminal pH of higher than 6.0 and thus, have little effect on microbial fermentation This result was in accordance with Hidayah et al (2014) who reported that the inclusion of different levels of sesame calcium soap, canola and flaxseed oils did not affect the pH level, ammonia and total VFA production of an incubated rumen. The role of calcium soaps supplementation to depress the negative effects of unsaturated fatty acids in the rumen ecosystem was possible due to a stable bonding of ionic calcium (Ca) and unsaturated fatty acids in the soap product which was insoluble in the rumen pH condition (neutral pH).…”
Section: Nutrient Digestibilitysupporting
confidence: 79%
“…The average variable values of rumen fermentation were in normal range which indicated that the supplementation of 5% SOCS and 10% CFF in the rations did not give significant negative effect on the digestion process in the rumen. Voigt et al (2006) reported that calcium salts of long-chain fatty acid are insoluble at ruminal pH of higher than 6.0 and thus, have little effect on microbial fermentation This result was in accordance with Hidayah et al (2014) who reported that the inclusion of different levels of sesame calcium soap, canola and flaxseed oils did not affect the pH level, ammonia and total VFA production of an incubated rumen. The role of calcium soaps supplementation to depress the negative effects of unsaturated fatty acids in the rumen ecosystem was possible due to a stable bonding of ionic calcium (Ca) and unsaturated fatty acids in the soap product which was insoluble in the rumen pH condition (neutral pH).…”
Section: Nutrient Digestibilitysupporting
confidence: 79%
“…Sirohi et al (2001) melaporkan bahwa penambahan minyak yang diproteksi dalam bentuk sabun kalsium dengan jenis berbeda yaitu minyak kedelai dan mustard plus mahua pada ransum berbasis jerami gandum memberikan respon sama terhadap kecernaan bahan pakan. Penambahan minyak dengan level 4% baik dalam bentuk bebas (tanpa p r o t e k s i ) d a n p r o t e k s i ( s a b u n k a l s i u m d a n mikroenkapsulasi), memberikan pengaruh yang sama terhadap KCBK dan KCBO (Hidayah et al 2014). Hal ini menandakan bahwa penambahan minyak pada level 4% dalam bentuk bebas belum mengganggu kecernaan bahan pakan.…”
Section: Populasi Protozoa Dan Bakteri Rumenunclassified
“…Menurut Mir et al (1997) penambahan minyak kanola pada pakan kambing atau sapi perah dapat meningkatkan kandungan CLA pada daging. Menurut Hidayah et al (2014) minyak laxseed dan minyak kanola memiliki ketahanan yang lebih tinggi terhadap proses biohidrogenasi didalam rumen. Hasil penelitian sebelumnya menunjukkan bahwa penambahan minyak kanola dan laxseed yang diproteksi dengan sabun kalsium pada taraf 4% tidak mengganggu populasi dan aktivitas mikroba rumen (bakteri dan protozoa) serta dapat meningkatkan aktivitas fermentasi mikroba rumen sapi potong.…”
unclassified
“…The fatty acids addition is one way to improve the feed energy. Hidayah et al (2014) found that the supplementation of flaxseed oil protected with calcium soap resulted the high total volatile fatty acid which is indicating the highest supply of energy for ruminant. Our previous study indicated that non protected sunflower oil addition as the sources of essential poly unsaturated fatty acid (PUFA) improved reproductive performance of ewes, but the mortality rate was still high on birth and pre weaning periods.…”
Section: Introductionmentioning
confidence: 96%